2022
DOI: 10.1093/cid/ciac510
|View full text |Cite
|
Sign up to set email alerts
|

Viral Dynamics of Omicron and Delta Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Variants With Implications for Timing of Release from Isolation: A Longitudinal Cohort Study

Abstract: Background In January 2022, United States guidelines shifted to recommend isolation for 5 days from symptom onset, followed by 5 days of mask wearing. However, viral dynamics and variant and vaccination impact on culture conversion are largely unknown. Methods We conducted a longitudinal study on a university campus, collecting daily anterior nasal swabs for at least 10 days for RT-PCR and culture, with antigen rapid diagnost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 22 publications
3
31
2
Order By: Relevance
“…Previous studies comparing the viable virus shedding periods of the Omicron and Delta variants found no significant difference between them (median 5 days in the Delta group vs. 4 days in the Omicron group, 5 median 3 days in the Delta group vs. 2 days in the Omicron group 6 ) which is not consistent with our present results (Figure 2 and Table 2 ). The shorter viable virus shedding period of patients with the Delta variant (median 5−6 days) is in line with our previous results in healthy young adults with SARS‐CoV‐2 Delta infections.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…Previous studies comparing the viable virus shedding periods of the Omicron and Delta variants found no significant difference between them (median 5 days in the Delta group vs. 4 days in the Omicron group, 5 median 3 days in the Delta group vs. 2 days in the Omicron group 6 ) which is not consistent with our present results (Figure 2 and Table 2 ). The shorter viable virus shedding period of patients with the Delta variant (median 5−6 days) is in line with our previous results in healthy young adults with SARS‐CoV‐2 Delta infections.…”
Section: Discussioncontrasting
confidence: 94%
“…Studies of the viral shedding kinetics of outpatients with asymptomatic or mild Delta or Omicron infections revealed comparable shedding durations. 5 , 6 However, these studies 5 , 6 were conducted in vaccinated patients without underlying medical conditions, and most of the patients had only mild symptoms or none at all. Although these data provide a useful basis for determining the duration of isolation of healthcare workers—who mostly have no underlying illness and have completed the initial vaccine series—they are of limited generalizability in terms of viable virus shedding kinetics in patients with Delta and Omicron infections, since the latter have variable clinical manifestations depending on age, underlying disease, and vaccination status in the real world.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent cohort studies comparing RAT and culture positivity found a 100% negative predictive value and 50% positive predictive value 4–6 days (n = 14) ( 20 ) and 6 days (n = 17) (L.A. Cosimi et al, unpub. data, https://doi.org/10.1101/2022.03.03.22271766 ) after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Cosimi et al found that only half of participants with a positive antigen test had a positive viral culture on day 6 following symptom onset [ 18 ]. Interestingly, that study, and another by Bouton et al, both report 100% negative predictive values for antigen testing with relationship to culture positivity [ 16 , 18 ]. Those studies provide reassuring data that those with a negative antigen test on day 6 are unlikely to be shedding viable virus.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to Tande et al, we found that being fully vaccinated and boosted was associated with antigen positivity compared with being unvaccinated [ 13 ]. While data demonstrate that boosted individuals are less likely to be infected with Omicron [ 14 ], emerging data suggest that those with breakthrough infections might have delayed viral decay and a longer time to viral clearance, which might explain our findings [ 15 , 16 ]. A longitudinal study evaluating viral load and culture positivity of the Omicron variant found a median time to culture conversion of 8 days and did not show differences in the median duration of viral shedding between those who were unvaccinated, fully vaccinated, and fully vaccinated and boosted, also suggesting that while vaccinations reduce the risk of infection, there might not be differences in viral kinetics during breakthrough infections with Omicron [ 17 ].…”
Section: Discussionmentioning
confidence: 98%